The Capacity of Tour Guides in Interpreting Marine Tourism-Based Tourist Attractions in South Sulawesi - Atriana Djabbar; Desrika Talib; Adinda Aulia Nursabila S (Program Studi S1 Pariwisata, Universitas Muhammadiyah Gorontalo, 2025)
This study aims to analyze the capacity of tour guides in interpreting Marine Tourism-based attractions in South Sulawesi, focusing on two representative locations: Salemo Island (Pangkep Regency) and Pannikiang Island (Barru Regency). The region holds significant Marine Tourism potential due to its rich marine ecosystems, coastal cultural heritage, and unique local attractions. However, the role of tour guides in translating this potential into meaningful, informative, and emotionally engaging narratives remains underdeveloped. A qualitative descriptive research method was employed using a thematic analysis approach. Data were collected through in-depth interviews with 3 (three) informants, participatory observation, and field documentation. Findings reveal that while several guides possess a basic understanding of ecological and cultural aspects, their interpretive delivery is often limited to one-way informational approaches, lacking visual aids and digital tools. There is a notable disparity in interpretive competency among guides, particularly in storytelling ability, two-way communication with tourists, and adaptability to environmental challenges such as adverse weather. Three main challenges were identified: the absence of adequate interpretive infrastructure, insufficient preparedness in managing on-site contingencies, and the lack of standardized interpretive training programs. To address these issues, the study emphasizes the importance of thematic training modules that include storytelling techniques, marine conservation principles, intercultural communication, and digital media integration. This research contributes to the discourse on sustainable Marine Tourism by positioning tour guides as key agents of educational engagement and environmental awareness. Strategic recommendations are proposed to strengthen interpretive capacity and foster the development of inclusive, meaningful, and environmentally responsible tourism experiences in South Sulawesi.